PENGARUH KUALITAS PEMBIAYAAN TERHADAP TINGKAT PROFITABILITAS PERBANKAN SYARIAH (STUDI KASUS PADA PT. BNI SYARIAH CABANG MAKASSAR) - sahran, sahran; Wahyuni, Sri (Universitas Muhammadiyah Makassar, 2019)
The results of this study are the quality of financing and the quality of human resources simultaneously have a significant effect on the effectiveness of income at PT. BNI Bank Syari'ah Makassar branch. The financing quality variable (X1) has a significant effect on the effectiveness of income (Y) at PT. BNI Bank Syari'ah Makassar branch. The variable quality of human resources (X2) has a significant effect on the effectiveness of income at PT. BNI Syariah Makassar branch. Between the independent variables and the dependent variable there is a strong relationship, this is evidenced by the value of the correlation coefficient (Multiple R), which means the higher the quality of financing and the quality of one's human resources, the higher the effectiveness of income positively. The coefficient of determination (R. Square) can be interpreted that changes in the two independent variables have a dominant influence on the dependent variable, while the remainder is caused by other variables not examined in this study.